Lafaz Al-Kawkab dalam Al-Quran dan Astronomi - Riri Hanifah Wildani; Sartika Fortina Ihsan; Efendi Bagindo Basa; Faizin Faizin (Program studi Keagamaan Islam, 2022)
Science is very closely related to revelation (the Qur'an), because both are sourced from Allah SWT. So this study aims to find a correlation between science, especially astronomy and revelation (Al-Quran) so that it can be a reference in view of the correlation between science and the Qur'an. Al-Qur'an contains miracles, one of which is I'jaz ilmi. I'jaz ilmi can be seen from the truth of the Qur'an which is proven in later scientific studies. This research is novel because it discusses the meaning of Lafaz al-Kawkab in the perspective of the Koran and the wisdom of its use in the Koran, as well as scientific facts about the planet. This research is descriptive qualitative, while the type of this research is library research. The method used in this study is the Tafsir Muqaran method, which compares various interpretations in the Tafsir books and captures their correlation with science. The results of this study stated that lafaz al-kawkab means planets in the solar system and has a different essence from other celestial bodies. In addition, the Qur'an also describes the nature and characteristics and functions of these planets by distinguishing the term al-kawkab and other celestial bodies in their mention.